2021
DOI: 10.1038/s41598-020-80580-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of SiC/SiO2 core–shell nanowires with good optical properties on Ni/SiO2/Si substrate via ferrocene pyrolysis at low temperature

Abstract: In this study, the high-density SiC/SiO2 core–shell nanowires were synthesized on the nickel coated SiO2 (100 nm)/Si substrate by chemical vapor deposition (CVD) method with ferrocene precursor at temperature 1000 °C compared to previous studies (1300–1600 °C). The present work provides an efficient strategy for the production of SiC/SiO2 nanowires with uniform morphology and good optical properties, where the Ni layer plays important roles for this fabrication at low temperature which reduces the decompositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…Previously, Tateyama et al and Pujar and Cawley reported that the SFs peak increases while the one related to (200) planes decreases with an increase in SFs density. The SFs content (χ) in SiC can be determined according to χ = I SFs / I (200) , where I SFs and I (200) are peak intensities related to SFs and (200) planes, respectively. , Moreover, Seo et al calculated the SFs density ( Y ) in terms of χ using eq . , Y = χ a χ + b + c χ 3 .25em ( % ) where χ presents the SF’s content, with values of a = 6.82 × 10 –2 , b = 2.27 × 10 –2 , and c = 1.7. Figure b shows the magnified XRD patterns from 32 to 44°, and the χ values are 0.79, 1.24, 1.81, and 1.32 for SiC@SiO 2 NWs-0, SiC@SiO 2 NWs-5, SiC@SiO 2 NWs-15, and SiC@SiO 2 NWs-30, respectively (Figure c), corresponding to SFs densities of 11.2, 14.8, 22.5, and 15.6%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, Tateyama et al and Pujar and Cawley reported that the SFs peak increases while the one related to (200) planes decreases with an increase in SFs density. The SFs content (χ) in SiC can be determined according to χ = I SFs / I (200) , where I SFs and I (200) are peak intensities related to SFs and (200) planes, respectively. , Moreover, Seo et al calculated the SFs density ( Y ) in terms of χ using eq . , Y = χ a χ + b + c χ 3 .25em ( % ) where χ presents the SF’s content, with values of a = 6.82 × 10 –2 , b = 2.27 × 10 –2 , and c = 1.7. Figure b shows the magnified XRD patterns from 32 to 44°, and the χ values are 0.79, 1.24, 1.81, and 1.32 for SiC@SiO 2 NWs-0, SiC@SiO 2 NWs-5, SiC@SiO 2 NWs-15, and SiC@SiO 2 NWs-30, respectively (Figure c), corresponding to SFs densities of 11.2, 14.8, 22.5, and 15.6%.…”
Section: Resultsmentioning
confidence: 99%
“…Various methods have been explored for the synthesis of SiC@SiO 2 NWs, including sol–gel, , chemical vapor deposition (CVD), , carbon thermal reduction, chemical etching, molten salt, , and thermal evaporation. , For example, Tian et al synthesized SiC@SiO 2 NWs by the CVD method using coconut cell and silicon (Si) as carbon (C) and Si sources, respectively, which emit strong violet-blue light and have good application prospects in optoelectronic devices. However, the productivity and purity are not satisfactory .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous research [ 43 ], the diffraction peak at 33.7° is caused by stacking faults on the (111) surface of 3C-SiC. Chen et al [ 44 ] evaluated the stacking fault density ( X ) by the intensity ratio of the SFs peak to the SiC (200) peak, as shown in Equation (1): …”
Section: Resultsmentioning
confidence: 99%
“…The PL spectra in 4H-SiC originate from a combination of phonon-instigated electronic transitions caused by defects in SiC [9][10][11]. This observation of luminescence quenching is not evidence of electronic doping [12,13]. Therefore, it is necessary to determine the additional factors that affect the PL quenching and luminescence properties of 4H-SiC by characterizing it fully.…”
Section: Introductionmentioning
confidence: 99%